Rural Development and Entrepreneurship: Exploration of Entrepreneurial Intention in Rural Area Among Chinese University Students - Wang He; Liang Ding (SAGE Open, 2023)
China’s rapid economic growth and correlating growth of metropolitan areas has attracted young people leaving their hometowns from the rural areas. Revitalizing the rural areas has been a national development strategy in China. College students returning home to start businesses is one way to alleviate the current shortage of young talents in rural areas of China. Based on the model of goal-directed behavior (MGB), this paper takes behavioral attitude, subjective norms, positive expectations of emotion, negative expectations of emotion, perceived behavioral controls, and government support, all as independent variables. The paper uses the desire as the intermediary variable to construct a goal-oriented behavior model about the intention of entrepreneurial initiatives by college students. By using survey data, the empirical analysis shows that the model has a strong explanatory power on the intention of college students. The positive expected emotions, perceived behavioral control, and government support, have a significantly positive influence on college student’s intentions through controlling behavior desire. The perceived behavioral control and behavioral desire of the subjects had a direct positive and significant influence on their intention. This research provides a reference for the government to formulate policies to attract college students to return to their hometowns to start businesses and boost rural revitalization.